Fitness club members: a “forgotten” target group for cardiovascular prevention? - A. E. Kutuzova; E. A. Kalinina; N. N. Petrova; A. O. Nedoshivin (Российский кардиологический журнал)
Aim. To assess physical and mental health status of the fitness club members. Material and methods. The study included 156 fitness club members (125 women, mean age 31±1 years; 9 men, mean age 39±5,5 years) who were interviewed in order to assess their medical history and physical activity levels. All participants underwent anthropometry and 3-minute Tecumseh step test. The Hospital Scale of Anxiety and Depression, Haim questionnaire on coping strategies, and visual analogue scale were also used. Results. The respondents considered themselves as having low levels of physical activity. “Heart disease” was reported by 16% of women. While 7,2% of women under 50 and 64% of women aged 50+ were aware of their high blood pressure, antihypertensive therapy was mentioned only by 9% of respondents. In women aged 50+ and in men, the values of body mass index were classified as obesity. Based on the step test results, “excellent” levels of exercise capacity were registered in 7,7%, “very good” in 6,5%, “good” in 7,7%, “satisfactory” in 26%, “poor” in 11,8%, and “very poor” in 40,3%. Hypertensive reaction to physical stress was observed in 27% and 5% of women aged under 50 and 50+, respectively. Almost one-fourth of women under 50 demonstrated affective disorders, predominantly anxiety, and a tendency towards non-constructive coping behaviour models. Individual goals of physical training were not always aligned with objective needs of the fitness club members. Conclusion. The physically active population group which attends fitness clubs demonstrated the presence of such cardiovascular risk factors as high blood pressure, overweight and obesity, and affective disorders. Fitness club members should receive regular compulsory consultations of the sports medicine specialist, in order to individualise the training programme, to identify people with low exercise capacity and pathological stress reaction (“risk group”), and to increase the safety of the fitness training process. To identify potential additional measures of cardiovascular prevention in physically active population groups, further research is warranted on physical and mental health of fitness club members.